The Effect of Open Unemployment Rate on GDP Per Capita in Medan City for the Period 2015–2024 - Biwi Cahya Wigrha; Annisa Ilmi Faried (Cattleya Darmaya Fortuna, 2026)
This study investigates the influence of the Open Unemployment Rate (OUR) on Gross Regional Domestic Product (GRDP) per capita in Medan City over the 2015–2026 period. A quantitative descriptive-associative approach was applied using secondary time-series data from the Central Bureau of Statistics (BPS) of Medan City, encompassing eleven years of observation with two projection years (2025–2026). Simple linear regression, t-test, and the coefficient of determination (R²) served as the primary analytical tools. The resulting regression equation is Y = 42.714 + 6.769X with R² = 0.247, indicating that OUR explains only 24.7% of the variation in GRDP per capita. The significance test yields p = 0.144 > 0.05, leading to the acceptance of the null hypothesis: the OUR exerts no statistically significant effect on GRDP per capita in Medan. The city's economic dynamics are predominantly shaped by the trade-and-services sector structure, investment flows, inflationary pressure, and regional fiscal policy interventions (Faried, Hasanah, & Fadlan, 2022). Policy implications underscore the importance of productive-sector-oriented development strategies to foster inclusive and sustainable labor absorption.